Buying airline partners: parallels between Swissair and Etihad Airways - Ellis, Darren; Foster, Andy (Elsevier, 2023)
During the 1990s Swissair adopted an alliance business model through the purchase of minority stakes in a number of carriers. Etihad Airways followed a similar approach from 2011 through until the onset of the Covid-19 pandemic, building equity stakes in a range of carriers in Europe, and the Indo-Pacific region. This paper uses comparative case study analysis, and argues that making substantial equity investments in second-tier (often loss-making or debt-laden) airlines increases risk without offsetting benefits. Viable alternatives to equity stakes exist including code-sharing, strategic partnerships and global alliance membership, that generate equally attractive customer perceived benefits, while avoiding the need for financial capital being applied less efficiently. Furthermore, this paper argues that profitability is not directly linked to alliance membership. Return on investment is arguably even harder to achieve when the alliance is based on a small selection of second tier carriers. The paper concludes with several future scenarios that could play out for airlines contemplating equity-based alliances, and identifies membership of one of the larger global alliances as the probable better option.
12th International Conference on Air Transport – INAIR 2023, The Future of Aviation – is the Sky the Limit? 15-17 November 2023, Tartu, Estonia
Keywords: Swissair; Etihad Airways; equity stakes; airline partnerships; global alliances